Analisis Risiko Usahatani Kelapa Sawit di Kecamatan Sematu Jaya Kabupaten Lamandau - Roni Ismoyojati; Nur Ikhsan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Oil palm plants, as a leading commodity in the plantation sector in Indonesia, play a significant role in economic growth. Risks in running an oil palm farming business are very likely to occur and can cause losses if not managed properly and correctly. This research activity was conducted in Sematu Jaya District, Lamandau Regency, Central Kalimantan Province, in March-May 2024. This research aimed to determine how much risk is posed by oil palm farming carried out by farmers in Sematu Jaya District. Research locations were randomly selected (Purposive Sampling), and three villages were selected from 8 existing villages. The number of respondents was determined using a simple random sampling method, with 42 farmers as respondents. The data obtained from this research comes from secondary and primary data. Primary data was analyzed using income analysis, coefficient of variation (CV), and descriptive analysis. The research results show that the production variation coefficient (CV) is 0.141 and the income variation coefficient (CV) is 0.0001371, which means that the risk of oil palm farming on production factors and income factors is low (<0.5). The lower limit value for production is 10.49 Tons/Ha/season/year, and the lower limit value for income is IDR15,576,180 Ha/season/year, which means avoiding losses (lower limit value >0). The advice for oil palm farmers in Sematu Jaya Regency is to minimize the risks posed by production factors by minimizing the purchase of unnecessary tools or materials with fixed costs and variable costs to reduce income risks.